Academic Senate Minutes 2007-09-27 - Academic Senate:::::::::
The Consent item, Revision to the Global Studies Program was approved. Susan Moulton was elected to the Executive Committee. The President gave a report. There was a discussion about the current WASC accreditation process. The Standing Committees and Associated Students representative gave reports. Revisions to the Cheating and Plagiarism policy completed a first reading.